Evaluation and reporting of CSR in the SME sector = Ewaluacja i raportowanie CSR w sektorze MŚP - Szczanowicz, Justyna; Saniuk, Sebastian (Zielona Góra: Faculty of Economics and Management Press)
This article is an attempt to propose a CSR evaluation and CSR reporting model in small and medium-sized enterprises. Special attention was given to trends which reveal the need for CSR development in practice with particular emphasis on efficiency - understood in two aspects: first one related to social welfare and sustainable development and the second one as a competitive advantage.
Keywords: społeczna odpowiedzialność biznesu; małe i średnie przedsiębiorstwa; CSR w sektorze MŚP; ewaluacja; raportowanie CSR; corporate social responsibility; CSR; small and medium enterprises (SME); evaluation; reporting